Reducing greenhouse gas emissions and improving rice yield: The influence of cultivars, soil salinity, and nitrogen management - Islam, S.M. Mofijul; Gaihre, Yam Kanta; Islam, Mohammad Nazrul; Suvo, Tamal Patra; Sander, Bjoern Ole; Habib, Muhammad Ashraful; Islam, Aminul; Nayak, Swati; Singh, Upendra; Hasegawa, Toshihiro; Islam, Md. Rafiqul (Elsevier BV, 2025)
Greenhouse gas emissions from rice cultivation are a significant contributor to climate change. Therefore, it is essential to consider effective mitigation strategies. A multi-location field experiment was conducted in Bangladesh over two consecutive Boro (dry) and Aman (wet) seasons, examining four rice cultivars and two nitrogen rates in both non-saline soils of Gazipur and coastal saline soils of Satkhira. The results indicated that BRRI dhan67 reduced methane (CH4) emissions by 11–14 % at 139 kg N ha−1 and by 9–12 % at 174 kg N ha−1 compared to BRRI dhan50 and BRRI dhan92 in the Boro season. Similarly, BRRI hybrid dhan3 reduced emissions by 6–9 % at 139 kg N ha−1 and by 11–14 % at 174 kg N ha−1 relative to BRRI dhan50 and BRRI dhan92. In the Aman season, BRRI dhan75 and BRRI hybrid dhan6 reduced CH4 emissions by approximately 10–14 % and 7–11 %, respectively, compared to BRRI dhan87 and BRRI dhan90. The impact of rice cultivars on nitrous oxide (N2O) emissions was insignificant in both seasons. A 20 % reduction in nitrogen from the recommended rates resulted in a 6 % decrease in CH4 emissions and 17 % decrease in N2O emissions, with no significant yield loss. Across cultivars and nitrogen rates, coastal saline soils emitted about 10 % less CH4 (p < 0.05) than non-saline soils. However, non-saline soils in Gazipur yielded about 11 % more and had around 13 % higher total nitrogen uptake than coastal saline soils in Satkhira. This study highlights the potential of climate-smart rice cultivars and optimized nitrogen management in promoting sustainable, low-emission rice cultivation in both saline and non-saline environments.